MEASURING THE AGREEMENT LEGALITY BETWEEN THE COMPANY OF ONLINE TRANSPORTATION SERVICE PROVIDER AND THEIR DRIVER PARTNERS IN EFFECTUATION OF NON-ROUTE PUBLIC TRANSPORTATION - Baco, Syamsuddin; Syamsuddin, Adiesty Septhiany Prihatiningsih; Noko’e, Nurhayati Sutan (Tadulako Law Review, 2018)
The increase of the online transportation practice raises problems from its legal aspects. Even so, the community actually welcomes it as an alternative means of public transportation, which is faster, cheaper and more convenient for the community.This study aims to: (1). Analyze the legal relationship of the online transportation service provider and their driver partners according to Indonesia Transportation Law; and (2) Analyze the validity and legality of the agreement between the company of online transportation service provider and their driver partners and also between the driver partners and their passenger and it relations under Indonesia Traffic Law.This research was conducted using normative legal approach with studies from theoretical, historical, structural and philosophical aspects of laws and regulations. Empirical approach was used to support the normative approach arguments.The results reveals that: (1) Construction of the legal relationship between the online transportation service provider and the drivers is an agency agreement, where the online transportation service provider act as a commercial agent (Agentuur) and the drivers act as the Principal. Therefore, the agreement substance that contained in the terms and conditions in the electronic contract categorized as an agency agreement (Agentuur contract). (2) The legal relation between the company of online transportation service provider and their driver partners and also between the driver partners and the passenger is a violation of Indonesia Traffic Law. Therefore, the legal status is null and void by law and the parties cannot file a lawsuit before the court based on that agreement